Physiological Responses and Ovarian Development of Female Chinese Mitten Crab Eriocheir sinensis Subjected to Different Salinity Conditions - Long, Xiaowen; Wu, Xugan; Zhao, Lei; Ye, Haihui; Cheng, Yongxu; Zeng, Chaoshu (Frontiers in Physiology, 2018)
Salinity plays a key role affecting ovarian development, osmoregulation and metabolism of female Chinese mitten crab, Eriocheir sinensis during reproductive migration. In this study, female E. sinensis after their puberty molt were subjected to four salinities of 0 ‰, 6 ‰, 12 ‰ and 18 ‰ for 40 days to investigate the salinity effects on their ovarian development as well as a range of important physiological parameters. Elevated salinity accelerated the ovarian development with ovigerous crabs found at salinity treatments of 12 ‰ and 18 ‰ despite no copulation had occurred. Meanwhile the survival rate of female crabs showed a decreasing trend with increasing salinity. Higher salinity also led to increased hemolymph Na+, K+, Ca2+, Cl- and Mg2+ concentrations. The 6 ‰ treatment had the highest contents of hemolymph total and major free amino acids while the Na+/K+ -ATPase activity in the posterior gills was the lowest among treatments. Total n-3 polyunsaturated fatty acids (∑n-3PUFA) and n-3/n-6 PUFA ratio in the anterior gills showed a decreasing trend with salinity while 18 ‰ had the highest ∑PUFA and ∑n-6PUFA. The ∑n-3PUFA content and n-3/n-6 PUFA ratio of the posterior gills showed a fluctuating pattern and the highest value was detected at 0 ‰, while an increasing trend was found for the ∑n-6PUFA with increasing salinity. The hemolymph glucose showed a decreasing trend with increasing salinity and the highest total cholesterol in hemolymph was detected at 12 ‰. The 18 ‰ treatment had the highest levels of hemolymph γ-glutamyltransferase, alkaline phosphatase and acid phosphatase, as well as glucose, urea and acid phosphatase in hepatopancreas while the highest hemolymph superoxide dismutase and malondialdehyde were detected at 0 ‰. Overall, the results showed that salinity increase from freshwater to brackish conditions led to lower metabolism, accelerated ovarian development, and the appearance of ovigerous crabs without copulation in female E. sinensis post puberty molt.